2021
DOI: 10.21303/2461-4262.2021.001949
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the agility of the automotive industry supply chain in times of COVID-19: a case study

Abstract: In the early stages of the corona virus pandemic, business environment was changing rapidly. The Moroccan automotive industry was one of the export sectors most affected negatively by the corona crisis; it collapsed during the three months of confinement and the pandemic has created immense uncertainties in demand and disrupted global supply chains. Indeed, to save the automotive industry, Morocco relies on its competitiveness and challenges current supply models for supply chain agility in order to better pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…• Others include decision-making trial and evaluation laboratory (DEMATEL) (Miao et al 2014 ), Delphi (von der Gracht and Darkow 2013 ), dynamic programming (Zhang et al 2021 ), entropy analysis (Lu et al 2019 ), equilibrium displacement model (Xiao 2010 ), event sequence analysis (Sprecher et al 2017 ), fault tree analysis (Kumar and Havey 2013 ), failure mode, effects, and criticality analysis (FMECA) (Raab et al 2013 ), flow modelling (Lehmann et al 2011 ), fuzzy quality function deployment (Tamtam and Tourabi 2021 ), genetic algorithm and multi-choice goal programming (Razavi et al 2021 ), inductive case-based reasoning ensemble (ICBRE) (Li et al 2012 ), Petri-nets (Wang et al 2016 ), Pugh matrix approach and Monte Carlo simulation (Baležentis et al 2021 ), and Theory of Constraints (Yang et al 2009 )…”
Section: Resultsmentioning
confidence: 99%
“…• Others include decision-making trial and evaluation laboratory (DEMATEL) (Miao et al 2014 ), Delphi (von der Gracht and Darkow 2013 ), dynamic programming (Zhang et al 2021 ), entropy analysis (Lu et al 2019 ), equilibrium displacement model (Xiao 2010 ), event sequence analysis (Sprecher et al 2017 ), fault tree analysis (Kumar and Havey 2013 ), failure mode, effects, and criticality analysis (FMECA) (Raab et al 2013 ), flow modelling (Lehmann et al 2011 ), fuzzy quality function deployment (Tamtam and Tourabi 2021 ), genetic algorithm and multi-choice goal programming (Razavi et al 2021 ), inductive case-based reasoning ensemble (ICBRE) (Li et al 2012 ), Petri-nets (Wang et al 2016 ), Pugh matrix approach and Monte Carlo simulation (Baležentis et al 2021 ), and Theory of Constraints (Yang et al 2009 )…”
Section: Resultsmentioning
confidence: 99%
“…Focusing instead on the MEM industry, the available literature has provided some evidence on the automotive industry ( Tamtam and Tourabi, 2021 ; Ghadir et al, 2022 ), which is a very specific segment of this sector; hence, results of these previous studies are not always suitable for a direct comparison with the present paper. Having said that, it is first to be observed that the drop in the volumes handled for the MEM industry appears as less relevant compared to T&F. Similar considerations hold true for the service level delivered to customers: MEM companies suffered from poor service performance mainly at the very beginning of the pandemic period, corresponding to the lockdown of many countries, but the pre-Covid conditions were easily restored.…”
Section: Discussionmentioning
confidence: 92%
“…Two case studies in the fashion footwear context have been analyzed by Braglia et al (2022) , with the aim to investigate how companies in this field reacted to the disruption caused by the Covid-19 pandemic, so as to increase resilience in case of future disruptions. The papers by Tamtam and Tourabi (2021) and Ghadir et al (2022) have instead analyzed the effects of Covid-19 in the automotive industry. The former authors have focused on the agile capability of automotive companies in the pandemic period, while the latter authors have proposed an approach for prioritizing risks induced by Covid-19 in the automotive supply chain.…”
Section: Literature Analysismentioning
confidence: 99%
“…Por su parte, en una empresa de la industria automotriz marroquí, se buscó alinear a la empresa con los proveedores y clientes, así como trabajar en conjunto para lograr la agilidad organizacional, estratégica e individual, vinculando las prioridades competitivas, los atributos y los habilitadores de la cadena de suministro a partir de la adopción de un enfoque de implementación de funciones de calidad difusas (FQFD), además de las dos casas de la calidad (HOQ) para identificar los más apropiados; una vez dada la evaluación, se demostró que hay tres habilitadores que necesitan mayor atención: el cumplimiento de los procesos, la capacidad logística y de distribución, así como de las herramientas informáticas de apoyo (Tamtam y Tourabi, 2021).…”
Section: Revisión De Literaturaunclassified